Economic growth with political lobbying and wage bargaining - Tapio Palokangas (Institute for the Study of Labor (IZA), 2009)
This paper examines an economy with a large number of industries, each producing a different good. Technological change follows a Poisson process where firms improve their productivity through investment in R&D. The less there are firms in the economy or the more they can coordinate their actions, the higher their profits. Labor is used in production or R&D. All workers are unionized and their wages depend on relative union bargaining power. If this power is high enough, then there is involuntary unemployment. Both workers and firms lobby the central planner of the economy which affects firms' and unions' market power. The main findings of the paper can be summarized the follows. The central planner can increase its welfare either (a) by increasing the level of income or (b) by speeding up economic growth. If (a) is more effective than (b), then the central planner eliminates union power altogether to have full employment. On the other hand, if (b) is more effective than (a), then the central planner supports labor unions to promote cost-escaping R&D.
urn:nbn:de:101:1-2009041444
Keywords: F15; J50; O40; 330; Economic integration; labor unions; market power; endogenous technological change; Wirtschaftswachstum; Interessenpolitik; Gewerkschaft; Marktmacht; Lohnverhandlungen; Industrielle Forschung; Produktivität; Theorie